2012
DOI: 10.1016/j.jnoncrysol.2011.11.007
|View full text |Cite
|
Sign up to set email alerts
|

Facile preparation of graphene-based chitosan films: Enhanced thermal, mechanical and antibacterial properties

Abstract: Chitosan is considered a model polymer because of its excellent biocompatibility, biodegradability, antibacterial property and metal binding ability. Despite the favorable properties, the poor mechanical strength and the loss of structural integrity limits the applications of chitosan. Graphene's intrinsic low weight with excellent thermal stability makes it an ideal filler for reinforcing polymers. In this work, we prepared graphene oxide (GO) via Hummer's method and simplified Hummer's method using graphite … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
69
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 138 publications
(76 citation statements)
references
References 58 publications
3
69
0
Order By: Relevance
“…The GO sheets had probably crumpled during the exfoliation stage and remained in that position even after reduction. 56 The formation of RGO was further confirmed by XPS analysis. The C1s of GO as shown in Figure 4A demonstrates the highest intensity at the binding energy of 287.8 eV, which belongs to carbonyl functional groups.…”
mentioning
confidence: 80%
“…The GO sheets had probably crumpled during the exfoliation stage and remained in that position even after reduction. 56 The formation of RGO was further confirmed by XPS analysis. The C1s of GO as shown in Figure 4A demonstrates the highest intensity at the binding energy of 287.8 eV, which belongs to carbonyl functional groups.…”
mentioning
confidence: 80%
“…GBMs have been tested as antibacterial against food borne pathogens bacteria e.g., E. coli and S. aureus (Santos et al, 2012;Liu et al, 2012;Tang et al, 2013); opportunistic pathogens bacteria e.g., P. aerogenosa and Klebseilla sp. (Lim et al, 2012;Bykkam et al, 2013); plant pathogen e.g., Xanthomonas oryzae and against fungi e.g., C. albicans and C. tropical (Li et al, 2013). Also several studies demonstrated and developed an environment friendly, cost effective, simple method and green approaches for the reduction of GO using microbial cells such as E. coli, Shewanella and Yeast (Gurunathan et al, 2013;Wang et al, 2011;Khanra et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…They were able to achieve enhanced mechanical performance, but more importantly they have shown that after 24 h a significant delay in Pseudomonas aeruginosa was obtained. [171] Lim et al [172] also explored the ability of rGO and CHI nanocomposites to retard the growth of Pseudomonas aeruginosa . The achieved data revealed that bacterial growth was not dependent on the concentration and size of rGO and could be completely suppressed by the low concentration of rGO in the chitosan solution, leading to a maximum viability loss of 100%.…”
Section: Biomedical Applicationsmentioning
confidence: 99%